The Eficacy of the National Sports Act, 2023 - Joshua Baluku (Uganda Christian University, 2024)
The much-anticipated National Sports Bill was signed into law on August 17, 2023, marking a watershed moment in Uganda's sports sector. This act, currently known as the National Sports Act 2023, repealed the National Council of Sports Act, Chapter 48. Given that the repealed law was enacted in 1964, it was undoubtedly designed for a different era when sports were treated solely as a leisure activity, which explains why it was unable to address pressing issues such as betting, match fixing, sports disputes, broadcasting, image rights, merchandising, agents and doping that had emerged over time as a result of sports professionalization. A strong legal framework is essential in the sports business due to the global rise of amateur, professional and commercial sports. It is critical to understand how the legal system continues to influence the daily decisions of sports management, coaches, educators, athletes, and others, as well as how it affects the sports industry as a whole. Liability concerns are widespread among the stakeholders involved in sports stadium design, workforce management, and exercise equipment installation. The sports sector has grown into a significant contributor to the world economy. This has increased the stakes for all parties involved, making many issues—such as broadcasting rights and conflict resolution mechanisms—unavoidable. Athletes' careers have been on the verge of extinction in various circumstances due to a number of issues, such as inadvertent actions by the respective sport federation or doping cases that have effectively ended the athlete's career. Because it is an activity that brings nations together, it is critical to keep sports-related issues off the court. Understanding legal issues and the legal system is critical for any successful individual or business, regardless of size. Sport law is taught by reading and assessing reported cases that have been tried in court.